Authority of The Ministry of Law In The Dishonourable Dismissal of Notaries For Violations of The Code of Ethics - Artini, Dewa Ayu; Senastri, Ni Made Jaya; Renaya, Nengah (Dinasti Research, 2026)
A Notary is tasked with carrying out a crucial role in society and is therefore required to always maintain their conduct, honour, and dignity as a public official. According to Article 16 letter a, a notary must safeguard the interests of the parties involved in legal processes and act in a trustworthy, honest, thorough, independent, and impartial manner. The objectives of this research include identifying and analysing the sanctions imposed on notaries by the Honorary Council for violations of the Code of Ethics, as well as the authority of the Ministry of Law in supervising notaries with regard to such violations. The type of research used in this study is normative legal research, applying the Statute Approach, Analytical and Conceptual Approach, and Case Approach. The synergy among supervisory institutions, continuous education, transparency, and an effective appeal system will enhance the effectiveness of oversight and professional discipline. For notaries, the researcher suggests that in carrying out their profession and position as public officials, they are expected to understand and comply with the provisions of the laws and regulations of the established Code of Ethics. The Ministry of Law can strengthen coordination and establish an integrated reporting system with the Notary Honorary Council in handling alleged violations of the Code of Ethics, ensuring that public reports are followed up promptly and transparently and to give open information on the status of reports, thereby increasing public participation in maintaining the integrity of the notarial profession.